PENGARUH PENGGUNAAN LKS BERBASIS DIRECT INSTRUCTION DALAM PENDEKATAN RECIPROCAL TEACHING TERHADAP KOMPETENSI FISIKA SISWA KELAS XI SMA N 2 PAINAN - Wirda Hilwa (Universitas Negeri Padang, 2014)
This article based on research that title “ influence of using student worksheets (LKS) based of direct instruction in reciprocal teaching approach to physical competence of students in class XI of SMA N 2 Painan”. This research based of the problems are role of students in teaching and learning process is not optimal yet and limitation of training facilities to thinking like student worksheets (LKS). The type of this research is quasi experimental . The populations of this research were all students in class XI IA of SMA N 2 Painan who listed in the academic year 2013/2014. Sample of this research was selected by cluster random sampling technique and the class was selected as experimental class is XI IA2 and control class is IA1. The instrument is used to collect data is written test for cognitive domain and observation sheet for affective domain and performance assessment form for the psychomotor domain. Data analysis techniques which used in this research ware normality, homogenity, and equality of two average test at real level 0.05. The results of the data analysis of cognitive, affective and psychomotor domain show that there is influence of using student worksheets (LKS) based of direct instruction in reciprocal teaching approach to physical competence of students in class XI of SMA N 2 Painan.